Analysis of FAM in satisfaction of inpatient services - Muhammad Sabir Ramadhan; Nizwardi Jalinus; Refdinal Refdinal; Marsono Marsono; Yohanni Syahra; Asyahri Hadi Nasyuha; Buyung Solihin Hasugian; Erika Fahmi Ginting; Masyuni Hutasuhut (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Patients are the main object who must get the best service at a hospital, because the quality of hospital services determines the recovery of a patient and the quality of the hospital. The quality of hospital services has two components, namely the fulfillment of predetermined quality standards and the fulfillment of patient satisfaction. Hospitals must provide services that focus on patient satisfaction. Improving the quality of health services can be started by evaluating each element that plays a role in shaping patient satisfaction. The application of evaluation measures to patient care in each hospital is needed as an increase in the quality of service to patients. The analysis of the fuzzy associate memory method has the closeness of human reasoning to get solutions to various problems so that they are easy to apply and understand. Utilization of decision support system (DSS) analysis with fuzzy associate memory method can be used as an evaluation of the perception of each consumer complaint to measure the level of patient satisfaction.